An attenuated nocturnal blood pressure dipping is associated with pump dysfunction in a population of African ancestry - Ngema, Mandisa Vinolia (My University, 2021)
Background: Non-dipper pattern, defined as an absence of nocturnal decline in blood pressure, is associated with an increase in cardiovascular events. Salt-sensitivity has been reported as a key contributor to a non-dipping profile. In numerous occasions, non-dipping and salt-sensitivity has been investigated in populations with health conditions such as hypertension and renal dysfunction. In this study, we investigated the impact of non-dipping on the cardiovascular system by measuring carotid-femoral pulse wave velocity (PWV) as an index of arterial stiffness, and the ejection fraction (EF) in a salt-sensitive black population of African ancestry, with no health complications. Methods: Nine hundred and forty-eight participants were recruited from the metropolitan areas around Johannesburg. Pulse wave velocity and echocardiography measurements were measured. After 24-hour ambulatory BP measurements, 796 participants were selected because they had complete 24-ambulatory measurements. Data was categorized into normal and overweight/obese body mass index (BMI). Results: Of the 283 participants with normal BMI, 151 were non-dippers and 132 were dippers in the study. A stepwise multiple linear regression model was fitted with the normal BMI SBP dipping percentage as the dependent variable, and PWV and EF as independent variables. After adjusting for covariates, PWV showed a positive association (r 2 = 0.13; P = 0.04) and a strong negative association was demonstrated between SBP dipping percentage and EF (r 2 = -0.23; P = 0.001). Conclusion: An attenuated nocturnal fall in BP results to an increased in arterial stiffness and consequently left ventricular pump dysfunction in black normotensive non-dippers with normal BMI
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2021